2014
DOI: 10.1007/s00484-014-0826-4
|View full text |Cite
|
Sign up to set email alerts
|

Ameliorative effects of melatonin administration and photoperiods on diurnal fluctuations in cloacal temperature of Marshall broiler chickens during the hot dry season

Abstract: Experiments were performed with the aim of determining the effect of melatonin administration on diurnal fluctuations in cloacal temperature (CT) of Marshall broiler chickens during the hot dry season. Birds in group I (12L:12D cycle) were raised under natural photoperiod of 12-h light and 12-h darkness, without melatonin supplementation, while those in group II (LL) were kept under 24-h continuous lighting, without melatonin administration. Broiler chickens in group III (LL + melatonin) were raised under 24-h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 64 publications
0
5
0
Order By: Relevance
“…Clinical studies have shown that exogenous administration of MLT suppresses the physiological increase in T b observed during daytime [32,33] and has hypothermic properties at the dose of 5 mg/kg [34,35,36,37,38]. Similar results have been demonstrated in preclinical studies in diurnal animals in which administration of MLT acted as a hypothermic agent in the active/light phase in fat sand rats and Marshall broiler chickens [39,40]. However, the neurobiological mechanism through which MLT exerts this hypothermic effect, as well as the selective contribution of the three MLT receptor subtypes, are yet to be investigated.…”
Section: Introductionmentioning
confidence: 53%
“…Clinical studies have shown that exogenous administration of MLT suppresses the physiological increase in T b observed during daytime [32,33] and has hypothermic properties at the dose of 5 mg/kg [34,35,36,37,38]. Similar results have been demonstrated in preclinical studies in diurnal animals in which administration of MLT acted as a hypothermic agent in the active/light phase in fat sand rats and Marshall broiler chickens [39,40]. However, the neurobiological mechanism through which MLT exerts this hypothermic effect, as well as the selective contribution of the three MLT receptor subtypes, are yet to be investigated.…”
Section: Introductionmentioning
confidence: 53%
“…; Sinkalu et al. ). The high THI may render evaporative cooling mechanism ineffective in the broiler chickens.…”
Section: Discussionmentioning
confidence: 98%
“…The t cloacal values were recorded as an indicator of the core body temperature (Sinkalu et al. ), with the aid of a digital clinical thermometer (KRAUSE digital thermometer (R) , DK‐5550, Langeskov, Denmark). The t cloacal was measured, concurrently with the thermal environmental parameters for 3 days only, 1 week apart, in order to reduce the adverse effect of stress due to handling on the birds, known to increase the body temperature (Edgar et al.…”
Section: Methodsmentioning
confidence: 99%
“…The mechanism of action of AA has been linked to its antioxidant activity (Surai 2007), and ROS are generated in excess in birds exposed to heat stress (Kikusato & Toyomizu 2013). Therefore, it seems likely that AA scavenged the ROS produced in the birds subjected to heat stress (Sinkalu, Ayo, Abimbola, et al 2014;Sinkalu, Ayo, Adelaiye, et al 2014). Betaine, on the other hand, did not significantly alter CT values in broiler chickens, except at 14:00 h. That is, betaine may not be beneficial in reducing body temperature responses in broiler chickens exposed to heat stress.…”
Section: Ct Responses Of Broiler Chickensmentioning
confidence: 97%
“…CT was obtained (as a measure of core body temperature; Sinkalu, Ayo, Abimbola, et al 2014;Sinkalu, Ayo, Adelaiye, et al 2014) using a digital thermometer (Kruuse Incorporated, Denmark). The thermometer was inserted about 3 cm into the cloaca and tilted to make contact with the wall of the cloaca.…”
Section: Ct Measurementsmentioning
confidence: 99%